Microbial consortium with nitrogen fixing and mineral solubilizing attributes for growth of barley (Hordeum vulgare L.) - Tanvir Kaur; Rubee Devi; Sunil Kumar; Imran Sheikh; Divjot Kour; Ajar Nath Yadav (Heliyon, 2022)
Bioinoculants provide better opportunity for ecological farming practices to improve the plant growth and enhanced crop productivity. Different types of bioinoculants containing single microbial culture and multiple microbial strains in single formulation could be used for agricultural sustainability. The different efficient microbial strain in single formulation as a consortium is an emerging trend in the present era. The present study deals with the isolation of nitrogen fixing, phosphorus and potassium solubilizing microbes from rhizospheric soil and root's internal tissues of different cereal/pseudocereal crops and their application as a microbial consortium for the growth of cereal crops. A total of 152 rhizospheric and endophytic bacteria were isolated and screened for the plant growth promoting (PGP) traits of nitrogen fixation, solubilization of phosphorus, and potassium. Among all the isolates, nine were found to fix nitrogen, fifteen and eleven exhibited phosphorus and potassium solubilization activity, respectively. Three selected efficient bacterial strains were identified using 16S rRNA gene sequencing as Erwinia sp. EU-B2SNL1 (N-fixer), Chryseobacterium arthrosphaerae EU-LWNA-37 (P-solubilizer), and Pseudomonas gessardii EU-MRK-19 (K-solubilizer). The inoculation of these three bacterial strains on barley crop as single inoculum and as microbial consortium enhanced the growth and physiological parameters including root/shoot length and biomass, chlorophyll, carotenoids, phenolics, flavonoids and soluble sugar content in comparison with untreated control. The microbial consortium was found to be more effective as compared to single inoculum. The microbial consortium of nitrogen fixing and mineral solubilizing microbes could be used as biofertilizer for plant growth and soil health.